2020
DOI: 10.1097/md.0000000000022163
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pregnancy rate between natural cycle and hormone replacement cycle in patients who underwent frozen embryo transfer using 2 consecutive hormone replacement regiments

Abstract: For frozen embryo transplantation patients who failed to use hormone replacement cycle (HRC) transplantation for 2 consecutive times, the third time of transplantation was divided into 2 groups: HRC and natural cycle (NC), and the pregnancy rate of the 2 groups, especially the clinical pregnancy rate, was compared. Retrospective study of 174 patients in the reproductive medicine center of an affiliated hospital of Shandong University of Traditional Chinese Medicine between January 2015 and September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…A previous retrospective study that determined an association between endometrial thickness and placenta previa found that women with endometrial thickness more than 12 mm were more likely to have placenta previa (adjusted OR 3.74, 95%CI, 1.90–7.34) than women with endometrial thickness less than 9 mm [ 76 ]. Previous studies have reported that the endometrial thickness was thinner in women who conceived with frozen ET than in women who conceived with fresh ET [ 76 , 107 , 108 ]. Therefore, a possible mechanism for the decreased rate of placenta previa for women who conceived using frozen ET is the thinner endometrial thickness.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study that determined an association between endometrial thickness and placenta previa found that women with endometrial thickness more than 12 mm were more likely to have placenta previa (adjusted OR 3.74, 95%CI, 1.90–7.34) than women with endometrial thickness less than 9 mm [ 76 ]. Previous studies have reported that the endometrial thickness was thinner in women who conceived with frozen ET than in women who conceived with fresh ET [ 76 , 107 , 108 ]. Therefore, a possible mechanism for the decreased rate of placenta previa for women who conceived using frozen ET is the thinner endometrial thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other three groups, the HRT group having the lowest endometrial thickness at one day before transplantation. Two retrospective cohort studies also showed that the endometrial thickness was less in the HRT group than in the NC group (29,30).However, there was no statistical difference in the incidence of biochemical pregnancy, clinical pregnancy, miscarriage or live birth between the two groups(30), probably because endometrial thickness is not a decisive parameter for successful pregnancy (31). However, a study by Shaodi et al (2020) showed that to obtain optimal live birth rate, the endometrial thickness must remain within the range of 8.7-14.5mm as too thin or too thick endometrium would reduce the live birth live (32) .More studies are needed to address the effect of endometrial thickness on pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%